(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Ibrutinib is a potent and highly selective irreversible Bruton’s tyrosine kinase (BTK) inhibitor. It has transformed the treatment of B-cell lymphomas, particularly mantle cell lymphoma and chronic lymphocytic leukemia (CLL). It is thought that BTK is essential for the survival and activation of healthy and cancerous B-cells. In recent years, an oral BTK inhibitor called ibrutinib has emerged as a ground-breaking treatment for hematological malignancies such as CLL. The viability of ibrutinib, though, could not end there. This drug has been identified to inhibit several additional kinases linked to solid cancers (epidermal growth factor receptor, human epidermal growth factor receptor 2). Recent findings suggest that BTK may be a target for anti-solid tumor treatment. As a result, research has been done on ibrutinib, a BTK-inhibitor, as a potential treatment for solid tumors. This review provides an in-depth analysis of an intriguing medication, emphasizing its mechanism of action, metabolism, safety profile, clinical studies, authorized applications, and prospects in the future.